Live-attenuated bacteria as a cancer vaccine vector. (October 2013) - Toussaint, Bertrand; Chauchet, Xavier; Wang, Yan; Polack, Benoit; Gouëllec, Audrey Le
In the emerging field of active and specific cancer immunotherapy, strategies using live-attenuated bacterial vectors have matured in terms of academic and industrial development. Different bacterial species can be genetically engineered to deliver antigen to APCs with strong adjuvant effects due to their microbial origin. Proteic or DNA-encoding antigen delivery routes and natural bacterial tropisms might differ among species, permitting different applications. After many academic efforts to resolve safety and efficacy issues, some firms have recently engaged clinical trials with live Listeria or Salmonella spp. We describe here the main technological advances that allowed bacteria to become one of the most promising vectors in cancer immunotherapy.